Simplified orientation determination in ski jumping using inertial sensor data - Groh, B. H.; Weeger, N.; Warschun, F.; Eskofier, B. M. (Inertial Sensors and Systems 2014, 2014)
The determination of the orientation of the skis during ski jumping provides fundamental information for athletes, coaches and spectators. Athletes and coaches can improve the training and the jump performance. Spectators can obtain interesting facts and a more attractive way of jump visualization by an orientation and jump angle determination. Existing camera-based systems to determine jump angles require a complex setup and calibration procedure. In contrast, inertial sensor-based methods can provide similar information with a low-cost and easy maintainable sensor setup. In this paper, we describe the processing of inertial sensor data (3D accelerometer, 3D gyroscope) in order to obtain the 3D orientation of the skis of an athlete during the whole jump sequence. Our methods include a functional sensor calibration to deal with sensor misalignment and a quaternion-based processing of sensor data. Acceleration data are used to determine the start and end of the jump and specific periods for the functional calibration. Gyroscope data are used to obtain the current orientation of the skis in each step of the movement. The orientation determination is evaluated by comparing the IMU calculated angle of attack (pitch angle of moving system) with a high-speed camera system. Our results show a root mean square error of 2.0° for the right ski and 9.3° for the left ski. It can be assumed that this difference of accuracy is influenced by the simple 2D evaluation method and perspective-related errors. A 3D high-speed video system with an accurate 3D representation of the skis is discussed for further evaluation.